Tissue Doppler derived biphasic velocities during the pre and post-ejection phases: patterns, concordance and hemodynamic significance in health and disease - Alaa Mabrouk Salem Omar; Diana Maria Ronderos Botero; Javier Arreaza Caraballo; Ga Hee Kim; Yeraz Khachatoorian; Jaclyn Kliewer; Mohamed Ahmed Abdel Rahman; Osama Rifaie; Jonathan N. Bella; Edgar Argulian; Johanna Contreras (Cardiovascular Ultrasound, 2022)
Abstract Background Pre-(PRE) and post-ejection (POE) velocities by mitral annular tissue Doppler (TD) are biphasic and may be related to myocardial deformations. We investigated the predominance and concordance of TD-PRE and POE velocities and their effect on myocardial functions in controls and in heart failure (HF) patients. Methods Retrospectively, 84 HF patients [57.6 years, 28(33%) females, NYHA: 2.3 ± 0.6, EF: 55 ± 15%, 52(62%) preserved EF, and 32(38%) reduced EF], 42 normal young controls, and 26 asymptomatic age matched controls were included. Echocardiography was done and from mitral annular tissue Doppler recordings, the biphasic PRE and POE velocity signals were identified and compared between groups. Results While controls had almost always predominantly positive PRE and negative POE, HF had more negative PRE and positive POE. Moreover, almost all controls exhibited normal concordance (positive PRE and negative POE). HF exhibited more abnormal concordance which was significantly associated with worse NYHA, and parameters of diastolic and systolic functions. Opposite PRE and POE velocities correlated significantly in all groups (PREp vs POEn: young:r = 0.52, p < 0.001, age controls:r = 0.79, p < 0.001, HFpEF: r = 0.56, p < 0.001, HFrEF: r = 0.42, p = 0.018; PREn vs POEp: young: r = 0.25,p = 0.1, age controls: r = 0.42, p = 0.04, HFpEF: r = 0.43, p = 0.004, HFrEF: r = 0.61, p < 0.001) and the ratios PRE-P/N and POE-N/P correlated significantly with E/e’ in HF only. Conclusions In physiological state, TD signals are predominantly positive during PRE and negative during POE. Opposite PRE and POE velocities corelate, representing the PRE-generation and POE-reversal of shortening–stretch relationships, the attenuation of which in HF may be related to elevated LV filling pressures. In HF, partially or completely reversed concordance of PRE and POE is associated with progressive worsening of clinical and hemodynamic profiles.